Reduction of antibacterial toxicity through nanostructured carriers - Silveira, Moema Silva Reis; Sousa, Jonas Nascimento de; Rodrigues , Leonardo Guedes; Veloso, Rafael Pires; Rolim, Hercilia Maria Lins (Seven Editora, 2023)
Bacterial resistance to antibiotics is a global health problem that needs to be resolved through the discovery of new therapeutic strategies. With the advancement of nanotechnology, new formulations have been tested for the ability to potentiate the action of antibiotics in traditional use by delivering more appropriate concentrations or reducing the toxicity of these drugs. In addition, the advent of nanotechnology allowed new strategies to be implemented to combat microbial resistance. The objective of this work was to carry out a bibliographic survey of the most recent formulations tested in nanotechnology to reduce the toxicity of antimicrobials, especially antibacterials, and/or increase their therapeutic effectiveness. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-020